THE CONCEPT OF CONTRACTING AUTHORITY UNDER PUBLIC PROCUREMENT LAW AND PROBLEMS OF ACQUISITION OF SUCH STATUS IN NATIONAL LAW OF THE REPUBLIC OF LITHUANIA - Tvaronaviciene, Agne; Visinskis, Vigintas (European Scientific Journal, ESJ, 2014)
Over 7,500 entities having status of contracting authority operate in the Republic of Lithuania. The status of contracting authority binds the body to buy goods, services and works necessary to carry on its functions, following the Law on Public Procurement of the Republic of Lithuania, which has been harmonised with the requirements of the European Union legislation. For the organisation, the status leads to a significant additional administrative burden and difficulties in arrangement of activity, therefore designation of the contracting authority's criteria and application procedures thereof must be clear and unambiguous. Practice, however, raises a number of questions regarding acquisition of the status, which indicates a lack of efficacy of existing assignment procedure. In this Article, while analysing the legal provisions governing the issues of contracting authority’s status acquisition and loss, the concept of the contracting authority is being purified as well as ways to solve the most common problems arising in the practice of body’s inclusion into the list of contracting authorities are being identified.